Thermoacoustic tomography : principles and applications - Jiang, Huabei (IOP ebooks. 2020 collection., 2020)
This book provides a comprehensive overview of thermoacoustic imaging approaches. It describes the fundamentals of thermoacoustic tomography (TAT) including the theory on thermoacoustic effect, image reconstruction methods and instrumentation; details advanced approaches for quantitative TAT, which allows for the recovery of tissue conductivity and mechanical properties; explores the development of several image enhancing schemes including both software and hardware approaches; examines array-based TAT systems that are the foundation of fast 2D and 3D TAT; considers high-resolution TAT approaches and combinations of TAT with other imaging methods; addresses contrast agent-based molecular TAT; and discusses clinical applications and animal studies in the areas of brain, breast, joint, thyroid, liver and vascular imaging. This book is a valuable resource for students, academics, and industry specialists--including biomedical engineers, electrical engineers, physicists and mathematicians. Part of IPEM-IOP Series in Physics and Engineering in Medicine and Biology.